Enantiomer Selective Glucuronidation of the Non‐Steroidal Pure Anti‐Androgen Bicalutamide by Human Liver and Kidney: Role of the Human UDP‐Glucuronosyltransferase (UGT)1A9 Enzyme. (20th May 2013) - Grosse, Laurent; Campeau, Anne‐Sophie; Caron, Sarah; Morin, Frédéric‐Alexandre; Meunier, Kim; Trottier, Jocelyn; Caron, Patrick; Verreault, Mélanie; Barbier, Olivier
Abstract Bicalutamide (Casodex®) is a non‐steroidal pure anti‐androgen used in the treatment of localized prostate cancer. It is a racemate drug, and its activity resides in the (R)‐enantiomer, with little in the (S)‐enantiomer. A major metabolic pathway for bicalutamide is glucuronidation catalysed by UDP‐glucuronosyltransferase (UGT) enzymes. While (S)bicalutamide is directly glucuronidated, (R)bicalutamide requires hydroxylation prior to glucuronidation. The contribution of human tissues and UGT isoforms in the metabolism of these enantiomers has not been extensively investigated. In this study, both (R) and/or (S)bicalutamide were converted into glucuronide (‐G) derivatives after incubation of pure and racemic solutions with microsomal extracts from human liver and kidney. Intestinal microsomes exhibited only low reactivity with these substrates. Km values of liver and kidney samples for (S)bicalutamide glucuronidation were similar, and lower than values obtained with the (R)‐enantiomer. Among the 16 human UGTs tested, UGT1A8 and UGT1A9 were able to form both (S) and (R)bicalutamide‐G from pure or racemic substrates. UGT2B7 was also able to form (R)bicalutamide‐G. Kinetic parameters of the recombinant UGT2B7, UGT1A8 and UGT1A9 enzymes support a predominant role of the UGT1A9 isoform in bicalutamide metabolism. Accordingly, (S)bicalutamide inhibited the ability of human liver and kidney microsomes to glucuronidate the UGT1A9 probe substrate, propofol. In conclusion, the present study provides the first comprehensive analysis of in vitro bicalutamide glucuronidation by human tissues and UGTs and identifies UGT1A9 as a major contributor for (R) and (S) glucuronidation in the human liver and kidney.